Ketahanan Padi (Way Apo Buru, Sinta Nur, Ciherang, Singkil dan IR 64) Terhadap Serangan Penyakit Bercak Coklat (Drechslera oryzae) dan Produksinya - Achmad Djunaedy (Agrovigor, 2009)
The purpose of this research to determine the  resilience of rice plant varieties Way Apo Buru, Sinta Nur, Ciherang, Singkil and IR 64 to the attack of brown spots disease (Drechslera oryzae), and production. Results of research: 1) the resilience of rice varieties Way Apo Buru, Sinta Nur, Ciherang, Singkil, and IR 64 against Drechslera oryzae attacks respectively 5.93%, 3.70%, 4:44%, 5.93%, and 7:41%, 2). The attack rate affect  production that is  higher levels of attack or more sensitive plants, the lower production.